Climatic and taxonomic influences on cuticular leaf wax distributions and isotope values of common eastern North American tree species - Brett James Tipple (PANGAEA, 2021)
Carbon and hydrogen isotope values with molecular distributions of normal-alkanes (n-alkanes), carbon and nitrogen isotope values of bulk leaf material, as well as xylem water hydrogen and oxygen isotope values are presented from five co-occurring tree species. Species were collected during the 2006-growing season from a climate transect along the East Coast of the United States where high-resolution temperature, precipitation, and humidity data were available. Efforts focused on Acer rubrum, Platanus occidentalis, Juniperus virginiana, Pinus taeda, and Pinus strobus. In addition, meteoric water samples were collected from rivers, streams, and other bodies of water along the transect. Leaf wax n-alkanes were extracted, isolated, identified, and quantified following Tipple and Pagani, 2013 (Geochimica et Cosmochimica Acta, 111, 64-77). The average chain length of n-alkanes, carbon preference index, among other indices were calculated. The carbon and hydrogen isotope values of leaf wax n-alkanes were conducted following Tipple et al., 2018 (Oecologia, 187, 1053-1075) and Tipple and Pagani, 2013, respectively. The carbon and nitrogen isotope values of bulk leaf materials were measured according to Tipple et al., 2018. Xylem waters were extracted from woody stems and both the hydrogen and oxygen isotope values of xylem and meteoric waters were measured following Tipple and Pagani, 2013. The purpose of this study was to compare leaf wax distributions and isotope values along a climate transect to better understand the environmental factors and species extquotesingle effects responsible for the carbon and hydrogen isotopic compositions of terrestrial plant materials, as well as the factors that influence n-alkane chain length. This study focused on species that inhabit the same environments and co-occur along a climate transect. This design allowed for interspecies and intraspecies variation to be explored. Site selections for this study allowed for an assessment of the importance of precipitation and temperature, while limiting the effects of humidity and elevation.